2020
DOI: 10.37536/riecs.2020.5.1.187
|View full text |Cite
|
Sign up to set email alerts
|

Impacto de la donación renal de vivo en la evolución de la función renal del donante

Abstract: "Introducción: El trasplante renal de donante vivo representa la mejor opción terapéutica para los pacientes con Insuficiencia Renal Crónica Terminal (IRC). Sin embargo, la nefrectomía conlleva ciertos riesgos a corto y largo plazo para el donante vivo. En este estudio queremos evaluar el impacto de la donación sobre la función renal del donante. Material y Métodos: Evaluamos retrospectivamente a los donantes vivos renales en el periodo comprendido entre 2010 y 2018 en el Hospital Universitario Ramón y Cajal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The behavior of renal function after nephrectomy in the donor is well described, according to Prieto-Matienzo et al [12] at one month after nephrectomy 48.7% of their population presented a GFR of < 60 ml/min/1.73m 2 , classifying them as patients with CKD, of these same patients at one year after nephrectomy, only 34.4% of the cases had CKD, also demonstrating a recovery of renal function. While in the population studied by Rivas-Nieto et al [13] the same signi cant decrease in GFR was demonstrated up to the sixth month of follow-up with recovery at one year, but as in our study this increase continues to be signi cantly lower than the preoperative value.…”
Section: Discussionmentioning
confidence: 88%
“…The behavior of renal function after nephrectomy in the donor is well described, according to Prieto-Matienzo et al [12] at one month after nephrectomy 48.7% of their population presented a GFR of < 60 ml/min/1.73m 2 , classifying them as patients with CKD, of these same patients at one year after nephrectomy, only 34.4% of the cases had CKD, also demonstrating a recovery of renal function. While in the population studied by Rivas-Nieto et al [13] the same signi cant decrease in GFR was demonstrated up to the sixth month of follow-up with recovery at one year, but as in our study this increase continues to be signi cantly lower than the preoperative value.…”
Section: Discussionmentioning
confidence: 88%